Dream Jobs - Giordano Mion; Luca David Opromolla; Gianmarco Ottaviano (Institute of Labor Economics (IZA), 2020)
Understanding why certain jobs are 'better' than others and what implications they have for a worker's career is clearly an important but still relatively unexplored question. We provide both a theoretical framework and a number of empirical results that help distinguishing 'good' from 'bad' jobs in terms of their impact on a worker's lifetime wage income profile through wage jumps occurring upon changing job ('static effects') or through increases in the wage growth rate ('dynamic effects'). We find that the distinction between internationally active firms and domestic firms is a meaningful empirical dividing line between employers providing 'good' and 'bad' jobs. First, in internationally active firms the experience-wage profile is much steeper than in domestic firms, especially for managers as opposed to blue-collar workers. Second, the higher lifetime wage income for managers in internationally active firms relies on the stronger accumulation of experience that these firms allow for and on the (almost) perfect portability of the accumulated dynamic wage gains to other firms. Static effects are instead much more important for blue-collar workers. Finally, the distinction between internationally active and domestic firms is relevant also at a more aggregate level to explain cross-sectional differences in wages among workers and spatial differences in average wages across regions within a country.
Keywords: J30; M12; J62; F16; 330; good jobs; international experience; managers; sorting; wage growth; wage premium